A GIS-based high spatial resolution assessment of large-scale PV generation potential in China - Yang, Qing; Huang, Tianyue; Wang, Saige; Li, Jiashuo; Dai, Shaoqing; Wright, Sebastian; Wang, Yuxuan; Peng, Huaiwu (Applied energy, 2019)
•600 land conversion factors are used to estimate the large-scale PV potential.•The potential PV power generation in China is estimated to be 1.38874 × 1014 kWh.•China's eight developed coastal provinces account for 1% of generation potential.•Associated CO2 reduction could meet China’s emission reduction commitment.•Maximum PV scenario needs inter-regional transmission capacity reach 300 GW. The achievement of temperature control target requires a low carbon transition of global energy structure. While China is actively promoting the implementation of large-scale PV generation technology, there is still a lack of scientific knowledge of the generation potential in China. To address this deficiency, this study builds a GIS-based model with 600 land conversion factors incorporated to accurately estimate the large-scale PV power generation potential in China. The results show a potential installed capacity of 1.41 × 105 GW, corresponding to an annual power generation of 1.38874 × 1014 kWh or 21.4 times national electricity consumption in China 2016. If this potential were fully realized as a replacement for current fossil fuel-based power generation in China 2030, a reduction in China’s carbon intensity of 63–68% compared to 2005 would result, which is sufficient to meet China’s CO2 emission reduction commitment. On a provincial level, while generation potential in Northwest and Inner Mongolia together account for 86% of the total, China's eight economically developed coastal provinces only account for 1%. To achieve a maximum large-scale PV scenario in China 2030, the capacity of inter-regional transmission grids from Northwest region and Inner Mongolia to the regions with insufficient potential should reach an approximate 300 GW. Our study could provide decision-makers with the precise information on large-scale PV power generation map of China, and optimizing low carbon strategies and inter-regional power transmission for achieving sustainable development.